Jet impingement cooling on a rib-roughened surface using extended jet holes - Tepe, Ahmet Umit; Uysal, Unal; Yetisken, Yasar; Arslan, Kamil (Elsevier BV, 2020)
Abstract In this study, jet impingement cooling on a rib-roughened surface has been investigated experimentally. The aim of this study is to investigate the effect of extended jet holes on the heat transfer performance and flow characteristics of the jet impingement cooling on a rib-roughened surface. The studies have been conducted under turbulent flow condition (16,250 ≤ Rej ≤ 32,500). Transient Liquid Crystals (TLC) method has been employed to investigate the average and local Nusselt number (Nu) distributions on the surface of interest. Six inline arrays of jet impingement configuration have been examined as the jet impingement cooling system. Jet holes were extended towards the target surface with the nozzles. Various dimensionless nozzles to the target surface gaps (Gj/Dj = 1.0, 2.0, 3.0, 4.0 and 5.0) have been investigated. Rectangular cross-sectional ribs were located on the surface of interest for the augmentation of heat transfer. Experimental studies were conducted on the dimensionless rib height as Hr/Dj = 0.42. In addition, numerical studies were carried out to investigate the flow and heat transfer characteristics. The effect of various dimensionless rib heights (Hr/Dj) on convective heat transfer performance has also been investigated numerically. SST k-ω with low-Re correction turbulence model was used for solving turbulence equations. Average and local Nu number distributions, flow characteristics and Performance Evaluation Criterion (PEC) were examined in detail. Results were compared with the orifice plate (Gj/Dj = 6.0) jet impingement configuration. Results showed that SST k-ω turbulence model accurately reveals the experimental data. Application of extended jet holes is a feasible method for practical application of the jet impingement cooling, especially at relatively low dimensionless nozzle gap (Gj/Dj ≤ 4.0). Furthermore, improperly designed rib height has been found to diminish heat transfer performance.